The impact of informal living conditions on water quality in the Bloemfontein municipality - Pretorius, E.; de Villiers, G. du T (My University, 2002)
Nonpoint source pollution from developing communities can adversely affect the natural functioning of river ecosystems and thus have severe economic and health implications for downstream users. The causes and sources of nonpoint source pollution are situated within the socio-economic and institutional environment of the community. The socio-economic conditions under which the people in a developing community live and the implications that this has on the quality of the water resources were identified by means of a field survey in the study area. Although community members tend to be positively orientated towards the prevention of water pollution, the results indicate that misperceptions and ignorance exist with regard to factors that cause water pollution and degrade water resources. From the results of the survey it is apparent that the variety of factors underlying pollution from developing communities are highly inter-dependant and a holistic approach to identify and address these problems, as well as their impact on the water resource, is necessary. The impact of informal living conditions on water quality in the Bloemfontein municipality (PDF Download Available). Available from: https://www.researchgate.net/publication/254355442_The_impact_of_informal_living_conditions_on_water_quality_in_the_Bloemfontein_municipality [accessed Jan 28, 2016].
Published Article